Puch'iji anæun p'yæonji Chæong Ho-sæung sisæonjip = A letter not sent : the collected poems of Jeong Ho-seung - Chæong, Ho-sæung 1950- (Seoul Selection U.S.A. Inc., 2016)
For the first time, English-language readers can access the poems of Jeong Ho-seung, who has become one of Korea's most beloved poets since his literary debut in 1973. A total of 216 poems spanning over 40 years of poetic growth were released in two collections, presented side by side in English and Korean. Loved by readers of all ages, from teenagers to those in their 60s and 70s, Jeong's poems tell of humanity's innate loneliness, sadness, longing, love and pain. In the words of the translator, Jeong's poems "may sometimes be challenging, but above all they are moving, enlightening, and insightful